ANALISIS PRINSIP-PRINSIP EKONOMI MIKRO DALAM KONSEP PERMINTAAN MENURUT PERSPEKTIF ISLAM: SUATU KAJIAN STUDI PUSTAKA - Ningsih, Dian Wirna; Mahyarni, Mahyarni; Hardiansyah Siregar, Kiki (LPPM - STIE SAKTI ALAM KERINCI, 2025)
The concept of demand is one of the fundamental principles in microeconomics, explaining the relationship between the price of a good and the quantity demanded by consumers. From an Islamic perspective, the concept of demand is not solely based on rational economic considerations but is also influenced by moral, ethical, and Sharia (Islamic law) values. This study analyzes the microeconomic principles underlying the concept of demand from an Islamic viewpoint. Unlike conventional theory, which bases demand on price, income, and consumer preferences, Islamic economics emphasizes that demand is also guided by Sharia values such as halal-haram (permissibility), justice, public interest (maslahah), and moderation in consumption. This research employs a literature review method, examining both classical and contemporary sources, including the thoughts of al-Ghazali, Ibn Taymiyyah, al-Shatibi, M. Umer Chapra, and Adiwarman Karim, along with empirical studies on Muslim consumption behavior. The findings reveal that the Islamic concept of demand has a dual orientation: fulfilling material needs while preserving the objectives of maqasid al-shariah. Thus, demand in Islam is directed toward goods and services that are lawful, beneficial, and free from harm. The study concludes that the Islamic theory of demand offers a more ethical, just, and sustainable alternative to conventional theories, enriching the body of Islamic economic knowledge. Keywords: Islamic Microeconomics, Demand, Sharia Principles, Literature Review